1979
DOI: 10.1021/jm00192a013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2,3,4,4a,5,9b-hexahydro-1H-pyrido[4,3-b]indole derivatives and their central nervous system activities

Abstract: The synthesis and some pharmacological effects of cis- and trans-2-substituted 2,3,4,4a,5,9b-hexahydro-1H-pyrido[4,3-b]indole derivatives are described. In these derivatives, the substituents of the 2, 5 and 8 position, together with the relative configuration of the 4a and 9b position, influenced the potency of the central nervous system activities. A cis-2-[3-(p-fluorobenzoyl)propyl] analogue (5k) of carbidine (1) possessed not only thymoleptic-like biological activity but had more potent neuroleptic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…For example, cis-2,8-dimethyl-1,2,3,4,4a,9b-hexahydro-γ-carboline (Carbidine) is effective in the treatment of schizophrenia, alcohol psychoses, and withdrawal syndromes [186]. cis-2-[3-(p-Fluorobenzoyl)propyl]-8-methyl-1,2,3,4,4a,9b-hexahydro-γ-carboline has similar activity [187].…”
Section: Hexahydro-γ-carbolinesmentioning
confidence: 97%
“…For example, cis-2,8-dimethyl-1,2,3,4,4a,9b-hexahydro-γ-carboline (Carbidine) is effective in the treatment of schizophrenia, alcohol psychoses, and withdrawal syndromes [186]. cis-2-[3-(p-Fluorobenzoyl)propyl]-8-methyl-1,2,3,4,4a,9b-hexahydro-γ-carboline has similar activity [187].…”
Section: Hexahydro-γ-carbolinesmentioning
confidence: 97%
“…This is evidently due to the fact that the formed complex of borane with the secondary amine is hydrolyzed significantly more quickly than with the tertiary amine; in this case the hydrolysis can take place earlier than protonation of the indole ring and subsequent hydride transfer [137]. This is why reduction of the N-benzyl-substituted derivatives followed by catalytic debenzylation was used for the production of secondary trans isomers of hexahydro-γ-carbolines [122]. However, the use of CF 3 COOH (strong enough for the formation of the 3H-indolinium ion and the non-nucleophilic acid) makes it possible to obtain trans-hexahydro-γ-carbolines containing a secondary amino group at position 2 with yields greater than 80% by direct reduction [138].…”
Section: Synthesis Of Cis-derivativesmentioning
confidence: 97%
“…cis-1,2,3,4,4a,9b-Hexahydro-γ-carbolines can be obtained by catalytic hydrogenation of the corresponding tetrahydro-γ-carbolines over PtO 2 in dilute hydrochloric acid [122]. The method is not used often on account of the need for special equipment; moreover, the complexity of catalytic hydrogenation again involves the possibility of more extensive reduction, and it is not always possible to stop at the formation of the hexahydro-γ-carboline.…”
Section: Synthesis Of Cis-derivativesmentioning
confidence: 99%
“…Their chemical structure indicated that in the Stobadine molecule the position of 2-N (cf. To prepare the anticipated Stobadine metabolites, knowledge derived from the synthesis of some other 2,3,4,4a.5.9b-hexahydro-1Hpyrido[4,3-b]indole derivatives was exploited (Nagai et al, 1979). 1) was enzymatically attacked.…”
Section: Drug Metabolismmentioning
confidence: 99%